Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to solve the following limit? $$\lim_{N\rightarrow+\infty}\frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^N$$

share|improve this question
    
Are you familiar with Riemann sums associated to Riemann integrals? –  Did Aug 26 '12 at 12:44
    
There is a celebre limit that states that if $\lim_{n\to\infty} a_{n} = a \geq 0$ and $\lim_{n\to\infty} b_{n} = b \geq 0$ then we have that $ \lim_{n\to\infty} \frac{a_{1} b_{n} + a_{2} b_{n-1}+ \cdots +a_{n} b_{1}}{n} =ab.$ I think this could be an alternative. –  Chris's sis Aug 26 '12 at 15:44
add comment

2 Answers 2

Fix a positive integer $M$. Then for $N \geq M$, we have

$$ 0 \leq \frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^N \leq \frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^M. $$

Thus

$$ \begin{align*}0 &\leq \liminf_{N\to\infty} \frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^N \leq \limsup_{N\to\infty} \frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^N \\ &\leq \lim_{N\to\infty} \frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^M = \int_{0}^{1} x^M \; dx = \frac{1}{M+1}. \end{align*}$$

Now taking $M \to \infty$, both liminf and limsup vanishes. Therefore the limit converges to 0.


Here is a much simpler argument: Since $x \mapsto x^N$ is increasing for $x \geq 0$, we have

$$ \left(\frac{k}{N}\right)^{N}\frac{1}{N} \leq \int_{\frac{k}{N}}^{\frac{k+1}{N}} x^{N} \; dx. $$

Thus

$$ 0 \leq \frac{1}{N}\sum_{k=0}^{N-1}\left(\frac{k}{N}\right)^N \leq \sum_{k=0}^{N-1}\int_{\frac{k}{N}}^{\frac{k+1}{N}} x^{N} \; dx = \int_{0}^{1}x^N \; dx = \frac{1}{N+1}.$$

(Here the beginning point of the summation index is changed to $k = 0$ instead of $k = 1$, which makes no difference.) Thus taking $N \to \infty$ proves the vanishing of the limit.

share|improve this answer
    
@RagibZaman: I understood what you are pointing out. Since $x \mapsto x^M$ is increasing, $$ \frac{1}{N}\sum_{k=1}^{N-1}\left(\frac{k}{N}\right)^M \leq \int_{0}^{1} x^M \; dx,$$ which makes the argument much simpler. –  sos440 Aug 26 '12 at 13:11
    
Actually, I misunderstood the subtlety of the argument initially, which is why I deleted my comment. It was not as simple as I had thought since the right hand bound doesn't tend to $0$ with $N$ immediately, but rather it depends on $M$ as well. Luckily, you've turned my ignorant comment into another nice finish to you proof! –  Ragib Zaman Aug 26 '12 at 13:13
    
Again a nice & simple proof! (+1) –  Chris's sis Aug 26 '12 at 14:28
add comment

Fix some large $M$ and suppose $N>M.$ Split the series into the first $N-M-1$ and the last $M$ terms like this: $$ \frac{1}{N} \sum_{k=1}^{N-1} \left( \frac{k}{N} \right)^N =\frac{1}{N} \sum_{k=1}^{N-M-1} \left( \frac{k}{N} \right)^N +\frac{1}{N} \sum_{k=N-M}^{N-1} \left( \frac{k}{N} \right)^N .$$

The summand of the first sum is maximized for $k=N-M-1$ so

$$\frac{1}{N} \sum_{k=1}^{N-M-1} \left( \frac{k}{N} \right)^N< \frac{N-M-1}{N} \left( \frac{N-M-1}{N} \right)^N< \left( \frac{N-M-1}{N} \right)^N \to \exp(-M-1)$$

as $N\to \infty.$

The summand of the second sum is maximized for $k=N-1$ so $$\frac{1}{N} \sum_{k=N-M}^{N-1} \left( \frac{k}{N} \right)^N< \frac{M}{N} \left(\frac{N-1}{N} \right)^N < \frac{M}{N} \to 0$$

as $N\to\infty.$

Thus for sufficiently large $N$, we have $$ \frac{1}{N} \sum_{k=1}^{N-1} \left( \frac{k}{N} \right)^N < \exp(-M-1).$$

For any $\epsilon>0$ we could have chosen $M$ large enough so that $\exp(-M-1) < \epsilon,$ so the limit is $0.$

share|improve this answer
    
+1 for the nice estimation of a rapidly decreasing bound! –  sos440 Aug 26 '12 at 13:08
    
Nice answer. (+1) –  Chris's sis Aug 26 '12 at 14:28
    
thank you so much –  jany Aug 27 '12 at 0:38
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.